A Review of ENSO Influence on the North Atlantic. A Non-Stationary Signal - Rodríguez de Fonseca, Belén; Suárez Moreno, Roberto; Ayarzagüena, Blanca; López Parages, Jorge; Gómara, Íñigo; Villamayor, Julián; Mohino, Elsa; Losada, Teresa; Castaño Tierno, Antonio (MDPI journals, 2016)
The atmospheric seasonal cycle of the North Atlantic region is dominated by meridional movements of the circulation systems: from the tropics, where the West African Monsoon and extreme tropical weather events take place, to the extratropics, where the circulation is dominated by seasonal changes in the jetstream and extratropical cyclones. Climate variability over the North Atlantic is controlled by various mechanisms. Atmospheric internal variability plays a crucial role in the mid-latitudes. However, El Niño-Southern Oscillation (ENSO) is still the main source of predictability in this region situated far away from the Pacific. Although the ENSO influence over tropical and extra-tropical areas is related to different physical mechanisms, in both regions this teleconnection seems to be non-stationary in time and modulated by multidecadal changes of the mean flow. Nowadays, long observational records (greater than 100 years) and modeling projects (e.g., CMIP) permit detecting non-stationarities in the influence of ENSO over the Atlantic basin, and further analyzing its potential mechanisms. The present article reviews the ENSO influence over the Atlantic region, paying special attention to the stability of this teleconnection over time and the possible modulators. Evidence is given that the ENSO–Atlantic teleconnection is weak over the North Atlantic. In this regard, the multidecadal ocean variability seems to modulate the presence of teleconnections, which can lead to important impacts of ENSO and to open windows of opportunity for seasonal predictability.
Keywords: Atlántico (Región) - Atmósfera; ENSO; North Atlantic region; Western African Monsoon; Euro-Mediterranean rainfall; North Atlantic Oscillation; Atlantic Multidecadal Oscillation; Hurricanes; Stratosphere; Teleconnections; Non-stationarity